Financial Performance Analysis of the Sea and Coastal Freight Water Transport Sector Using the Entropy-Based COPRAS Method - İsmail Fatih Ceyhan; Ferhat Demirci (Journal of Transportation and Logistics)
Maritime transportation is very important for Turkey due to its geographical structure being surrounded by seas. Turkey’s most attractive aspects compared to other countries is that it allows for relatively low unit costs in the sector and can transport a variety of products. In addition to the macro targets set by legal authorities regarding sector development, operating companies must crucially also possess a sustainable financial structure. The aim of the research is to analyze the financial performance of the Turkish sea and coastal freight water transport sector for the 2009-2020 period. This period has been sorted using the COPRAS method, a multi-criteria decision-making method, in terms of financial ratios widely used in financial analysis. The weight values of the criteria have been calculated using the entropy method. When considering the entropy method’s findings, financial ratios related to profitability took on higher values than the other ratios. According to the findings, the most successful year in this period was 2012, and the least successful year was 2011. The study results generally conclude the sector to have shown variable financial performance during the period and the factors determining the financial performance ranking for this sector to be the profitability ratios.